THE CONTENT ANALYSIS OF OIL IN COASTAL WATER AND SEDIMENTS OF SUIR RIVER ESTUARY OF MERANTI ISLANDS - Fajri Ramayori; Syahril Nedi; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in July 2014 with the aim to analyze the oil content in the water and sediment in the Suir River Estuary in Meranti Islands. This study was expected to serve as the initial information about the oil content in the water and sediments and as a baseline for future research assesing marine pollution in the waters of the River Suir Estuary in Meranti Islands. The method used was a survey method. The oil content in the water was highest at Station 3 (0,15 ppm) which was located in the outer region of the Suir estuary, and the highest in the sediment was at Station 2 (1473,66 ppm) which was located in the central region of the River Suir Estuary. The lowest oil content in the water and sediments, was forward at Station 1 (0,035 ppm and 818,08 ppm), which is part of the Suir estuary. Oil content in the water did not show real relationship with the oil content in the sediment (Y = 1147 - 1493x), the coefficient of determination R2 = 0,05 and correlation coefficient r = 0,23 indicating a negative relationship. Oil content in water was lower than the value of the quality standards set by State Ministry of the Environmental Affairs (2004), the oil content in the sediment was lower than the threshold value has been determined by the National Academy of Science (2001).Keywords: Oil, Waters, Sediment, Suir, Meranti